Faktor-Faktor Yang Mempengaruhi Kemauan Membayar Pajak Wajib Pajak Orang Pribadi Pada Kantor Pelayanan Pajak Pratama Senapelan Pekanbaru - kamilah, faizah (Jurnal Daya Saing, 2016)
This study aimed to analyze the influence of consciousness of paying taxes, knowledge and understanding of tax laws on the willingness to pay taxes individual taxpayers who do the work free.The sample in this study are 100 individual taxpayers who do the work free on KPP Pratama Pekanbaru randomized using a sampling technique accidental sampling and then analysis of data obtained using the analysis of quantitative and qualitative data. Quantitative analysis includes: validity and reliability, the classic assumption test, multiple regression analysis, hypothesis testing through t test and F, as well as the coefficient of determination (R2). Qualitative analysis is the interpretation of the data obtained in the study and the results of data processing that has been carried out by giving a description and explanation. Statistical analysis showed that the consciousness of paying taxes, knowledge and understanding of tax laws partial and simultaneous positive and significant impact on will pay taxes. Keywords: Willingness to pay taxes, pay taxes awareness and knowledge of tax laws